PENGEMBANGAN DUSUN TULAUN MINAHASA SEBAGAI DESA WISATA - Jonathan Tambahani; Melga Tamboto; Sisilia Toisuta; Andra Galang Todano; Meita Rumbayan (MONSU'ANI TANO Jurnal Pengabdian Masyarakat, 2023)
The background issue of the Student Community Service Creativity Program (PKM-PM) activity in the village of Tulaun is the underdevelopment of this village as a tourist destination despite its abundant tourism potential. The objective of this community service activities is to provide a solution to the challenges faced by partners in developing the tourist village through the construction of supporting facilities, namely independent energy gazebos. The following are the approach strategies implemented in various stages, including: (1) Survey stage (2) Design planning stage (3) Gazebo material procurement stage (4) Gazebo construction stage (5) Independent energy gazebo facility installation stage. The result of the PKM activity is the introduction and installation of a solar-powered lighting system developed using a 50 WP solar panel capacity. A battery with a total capacity of 10 AH is used to store the generated electrical energy and as a source of energy for supplying power to the independent energy gazebo lighting. The implementation result of the PKM activity includes the enhancement of the Tulaun tourist village facilities in Minahasa and the promotion of renewable energy usage in the village